2023
DOI: 10.1007/s00784-023-04941-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexural strength, surface roughness, micro-CT analysis, and microbiological adhesion of a 3D-printed temporary crown material

Abstract: Objective: To evaluate the thermocycling effect of 3D-printed resins on exural strength, surface roughness, microbiological adhesion, and porosity.Materials and methods: Speci cally, 150 bar specimens (8 × 2 × 2 mm) and 100 blocks (8 × 8 × 2 mm) were made and divided among ve groups, according to two factors: "material" (AR: acrylic resin, CR: composite resin, BIS: bis-acryl resin, CAD: CAD/CAM PMMA resin, and PRINT: 3D-printed resin) and "aging" (non-aged and aged -TC). Half of the samples from each group wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“… Ultraviolet polymerization Digitally produced intermediate materials outperformed traditionally polymerized materials in terms of mechanical characteristics NA [ 31 ] 3-point flexural bend test SLA = 48.9 SLS = 77.3 Acrylic resin = 69.2 Bis-acryl resin = 75 Polymerized with light SLS resin demonstrated positive outcomes, showcasing higher maximum flexural strength Orientation angles and new types of resins were missing. [ 30 ] Universal testing machine Graphy = 329.3 NextDent = 177.8 NA 3D-printed resin crowns might present a viable alternative for fabricating fixed prostheses for primary teeth Study design [ 38 ] 3-point flexural bend test 3DCS = 143 3DOS = 141 CHP = 76 CAP = 88 Polymerization The tested 3D-printed interim resins outperformed the traditional resins A limited number of materials were investigated and tested [ 32 ] 3-point flexural bend test Cosmos Temp = 56.83 Evolux PMMA = 111.76 Structur 2 SC = 87.34 post-polymerized with 3000 flashes of ultraviolet light Although the mechanical qualities of the milled resin were more significant or comparable to those of the bisacrylic resin, the 3D-printed resin was statistically inferior to both the milled and bisacrylic resins Orientation angles were not considered [ 33 ] 3-point flexural bend test 3D printed = 81.33 Acrylic resin = 72.90 Nanofilled composite resin = 34.97 CAD/CAM PMMA resin = 94.63 Bis-acryl composite resin = 91.57. NA Except for 3D-printed resin, thermocycling lowered the flexural strength of most temporary materials NA [ 35 ] 3-point flexural bend test Before accelerated aging (pre-aging), the flexural strength of the A2 group (151 ± 7) was greater (p < 0.05) than that of the other groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Ultraviolet polymerization Digitally produced intermediate materials outperformed traditionally polymerized materials in terms of mechanical characteristics NA [ 31 ] 3-point flexural bend test SLA = 48.9 SLS = 77.3 Acrylic resin = 69.2 Bis-acryl resin = 75 Polymerized with light SLS resin demonstrated positive outcomes, showcasing higher maximum flexural strength Orientation angles and new types of resins were missing. [ 30 ] Universal testing machine Graphy = 329.3 NextDent = 177.8 NA 3D-printed resin crowns might present a viable alternative for fabricating fixed prostheses for primary teeth Study design [ 38 ] 3-point flexural bend test 3DCS = 143 3DOS = 141 CHP = 76 CAP = 88 Polymerization The tested 3D-printed interim resins outperformed the traditional resins A limited number of materials were investigated and tested [ 32 ] 3-point flexural bend test Cosmos Temp = 56.83 Evolux PMMA = 111.76 Structur 2 SC = 87.34 post-polymerized with 3000 flashes of ultraviolet light Although the mechanical qualities of the milled resin were more significant or comparable to those of the bisacrylic resin, the 3D-printed resin was statistically inferior to both the milled and bisacrylic resins Orientation angles were not considered [ 33 ] 3-point flexural bend test 3D printed = 81.33 Acrylic resin = 72.90 Nanofilled composite resin = 34.97 CAD/CAM PMMA resin = 94.63 Bis-acryl composite resin = 91.57. NA Except for 3D-printed resin, thermocycling lowered the flexural strength of most temporary materials NA [ 35 ] 3-point flexural bend test Before accelerated aging (pre-aging), the flexural strength of the A2 group (151 ± 7) was greater (p < 0.05) than that of the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in South Korea [ 1 , 29 , 30 ] and Brazil [ 31 33 ], followed by Saudi Arabia [ 34 , 35 ], China [ 36 ], Turkey [ 37 ], Romania [ 38 ], India [ 39 ], and Germany [ 40 ]. Most studies have employed Digital Light Processing (DLP) [ 30 , 33 , 35 , 38 , 40 ], stereolithography (SLA) [ 32 ], Both DLP and SLA [ 1 , 29 , 34 ], Fused Deposition Modeling (FDM) [ 1 ], and mono-liquid Crystal Display (LCD) [ 36 ], with a variety of printed materials, such as acrylic, composite resin, and methacrylate oligomer-based materials. The layer thickness was 50 μm in most studies [ 30 , 34 , 35 , 40 ], and the wavelength/light intensity varied across studies, with a maximum of 405 nm/13.14 mW/cm 2[ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average surface roughness value (Ra) was determined by measuring (µm) three regions identified at the center of the sample surface. Measurements were made at a speed of 0.5 mm/sec, with a cut-off measurement length of λc = 0.25 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Espinar et al confirmed that the optical properties of CAD/CAM hybrid 3D-printed restorations depend on thickness and building orientation [10]. Current in vitro studies on CAD/CAM hybrid 3D-printed restorations are mainly limited to static tests evaluating intrinsic material properties, such as material strength [11][12][13][14][15][16][17][18][19][20], resilience [16], fracture toughness [16,19], microhardness [11,21,22], wear [23], surface roughness [18,22,24], and modulus of elasticity [11,17]. No studies are available regarding the color determination of CAD/CAM hybrid 3D-printed teeth.…”
Section: Introductionmentioning
confidence: 99%